2003
DOI: 10.1007/s00244-002-2014-5
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Lead, Zinc, and Cadmium in a Wild Population of Clethrionomys glareolus from an Abandoned Lead Mine

Abstract: Lead, zinc, and cadmium were determined in a range of tissues from wild populations of bank voles (Clethrionomys glareolus) trapped on an abandoned metalliferous mine site and a reference site. Estimated dietary intakes indicated that animals were exposed to elevated levels of all three metals at the mine site, and this was generally reflected in metal residues in body tissues. Lead concentrations were significantly higher in all tissues of animals from the mine compared to the reference site, while Cd was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 25 publications
7
19
3
Order By: Relevance
“…In the liver and kidney of mice from the volcanic active area, the levels of those elements were so high that in the case of Pb they were very close to the ones found in bank voles from an abandoned lead mine in UK, and in mice and rats from a sulfur mine in Portugal mainland. In the case of Cd and Zn, levels found in the liver and kidney were 10-30 times and 2-6 times, respectively, higher to those of rodents from the abandoned mines mentioned before (Milton et al 2003; Viegas-Crespo et al Pereira et al 2006). The very high levels of Al, Cd, Pb, and Zn in mice from Furnas may result from the ingestion of food or soil rich in those metals but also from the inhalation of volcanic gases and aerosols that transport those elements (Durand and Grattan 1999;Ferreira and Oskarsson 1999;Durand et al 2004), as confirmed by the high levels found in the lung.…”
Section: Discussionmentioning
confidence: 53%
“…In the liver and kidney of mice from the volcanic active area, the levels of those elements were so high that in the case of Pb they were very close to the ones found in bank voles from an abandoned lead mine in UK, and in mice and rats from a sulfur mine in Portugal mainland. In the case of Cd and Zn, levels found in the liver and kidney were 10-30 times and 2-6 times, respectively, higher to those of rodents from the abandoned mines mentioned before (Milton et al 2003; Viegas-Crespo et al Pereira et al 2006). The very high levels of Al, Cd, Pb, and Zn in mice from Furnas may result from the ingestion of food or soil rich in those metals but also from the inhalation of volcanic gases and aerosols that transport those elements (Durand and Grattan 1999;Ferreira and Oskarsson 1999;Durand et al 2004), as confirmed by the high levels found in the lung.…”
Section: Discussionmentioning
confidence: 53%
“…Nevertheless, we did observe significantly higher blood lead levels in residents living around abandoned mines than in control subjects, suggesting probable exposure to heavy metals including lead from contaminated materials in the abandoned mines. A study of the health impact of living near abandoned mine areas in Spain (Alonso et al 2001;Mayan et al 2006), Sweden (Berglund et al 2010), France (Burbure et al 2003), and the UK (Milton et al 2003) also confirmed that environmental contamination due to abandoned metal mining remained a significant source of increased levels of lead in the blood of children, adults, and wild animals, suggesting the need for ongoing surveillance of these areas to prevent possible health effects, and to facilitate environmental remediation.…”
Section: Discussionmentioning
confidence: 81%
“…Lead affects a wide range of physiological systems and organs, including the central and peripheral nervous system, the cardiovascular system etc [71]. Lead produces an excessive amount of reactive oxygen species resulting in oxidative stress, thereby resulting in hypertension [13] and chronic kidney disease [80]. Lead has also multiple hematological effects as well as genotoxic effects [76].…”
Section: Lead -Toxic Effects On Animals and Humansmentioning
confidence: 99%